ANALYSIS OF MACROECONOMIC INDICATORS OF UZBEKISTAN, THE IMPORTANCE OF MACROECONOMIC STABILITY - Jabbarova Dilafruz Sodiq kizi (European Science Publishing, 2025)
The article explores various perspectives on the concept of macroeconomic policy, attempting to define it within the framework of strategic activities implemented by the state. In our view, the primary objectives of macroeconomic policy include controlling unemployment and inflation, balancing macroeconomic indicators, preventing economic crises, and ensuring the stable and efficient functioning of the economy. Efforts have been made to analyze the impact of state-implemented measures on improving macroeconomic indicators and stabilizing the economy, as well as to examine the measures aimed at promoting stability.
Keywords: Macroeconomic policy, unemployment and inflation, macroeconomic indicators, economic crises, stable economy, state measures, economic stability, strategic activities, balanced development, efficient management.